2006
DOI: 10.1177/095632020601700402
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Ribavirin and Interferon Alfacon-1 Therapy of Acute Arenaviral Disease in Hamsters

Abstract: Several arenaviruses endemic to South America (Junin, Machupo, and Guanarito) and Africa (Lassa) are known to cause frequently fatal haemorrhagic fever. With the exception of ribavirin, which has demonstrated efficacy in cases of Lassa fever, there is no other effective therapeutic for the treatment of arenaviral haemorrhagic fever. We have recently reported that consensus interferon-α α (IFN alfacon-1) can protect hamsters from lethal Pichinde virus (PCV) infection, which serves as a model for acute arenavira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Interestingly, our data showed that lower doses of ribavirin were more effective than T-705 for the treatment of PICV infection. We previously showed that 20 mg/kg/day oral ribavirin is the lower limit for optimal protection against PICV infection when treatment is initiated 24 h post-infectious challenge (11). Here, we have verified that finding and reported that 50 mg/kg/day was the lowest tested dose of T-705 that provided complete protection in the PICV infection model.…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, our data showed that lower doses of ribavirin were more effective than T-705 for the treatment of PICV infection. We previously showed that 20 mg/kg/day oral ribavirin is the lower limit for optimal protection against PICV infection when treatment is initiated 24 h post-infectious challenge (11). Here, we have verified that finding and reported that 50 mg/kg/day was the lowest tested dose of T-705 that provided complete protection in the PICV infection model.…”
Section: Discussionsupporting
confidence: 74%
“…A combination of ribavirin plus immune serum increased survival in LASV-infected monkeys, suggesting that this combination might be useful for treating human beings with LF [89]. The combination of IFN-alfacon-1 ( Escherichia coli -expressed human IFN-α) plus ribavirin had synergistic activity that slowed disease and reduced fatality rates in hamsters inoculated with the arenavirus, Pichindé [90], which serves as a small animal model for LF.…”
Section: Introductionmentioning
confidence: 99%
“…Although Lassa fever is thought to be resistant to the effects of type I IFN [20], a recent study demonstrated sensitivity of several strains Lassa virus to IFN-α and -γ in cell culture [21]. Moreover, treatment with consensus IFN-α, alone or in combination with ribavirin has proven effective in the hamster PICV infection model [22], [23]. A novel therapy based on the targeting of anionic phospholipids exposed on infected cells and virions has shown promise in studies employing a guinea pig model based on infection with an adapted PICV [24].…”
Section: Introductionmentioning
confidence: 99%